2017
DOI: 10.24126/jobrc.2017.11.1.512
|View full text |Cite
|
Sign up to set email alerts
|

Improving Conditions for Gliotoxin Production by Local Isolates of Aspergillus fumigatus

Abstract: Thirty two isolates of Aspergillus fumigatus were obtained from a total of 44 samples of sputum, nose swab and tracheal aspirate from suspected patient with aspergillosis were also collected from February 2014 to June 2014.  A morphological examination of A. fumigatus was first made with naked eye and at low magnification power of microscope after that detailed examination was done by measuring the dimensions of the microscopic structures, photographing the microscopic structures and using relevant literature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…Aspergillus fumigatus produces an extremely toxic metabolite called gliotoxin [ 59 ]. We selected YES medium for evaluating gliotoxin production because Dheeb [ 60 ] and Hussain [ 61 ] found that for gliotoxin production, YES was ideal, probably due to its components, particularly carbohydrates (4% sucrose as a source of carbon) and yeast extract (2%).…”
Section: Discussionmentioning
confidence: 99%
“…Aspergillus fumigatus produces an extremely toxic metabolite called gliotoxin [ 59 ]. We selected YES medium for evaluating gliotoxin production because Dheeb [ 60 ] and Hussain [ 61 ] found that for gliotoxin production, YES was ideal, probably due to its components, particularly carbohydrates (4% sucrose as a source of carbon) and yeast extract (2%).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer occurs when cells in that gland undergo genetic changes (mutations). Mutations allow cells to grow and multiply rapidly (Hussain et al, 2017). These cells do not die as normal cells do.…”
Section: Goitermentioning
confidence: 99%